Alpha-smooth muscle actin and serotonin receptors 2A and 2B in dogs with myxomatous mitral valve disease. (June 2015) - Cremer, S.E.; Moesgaard, S.G.; Rasmussen, C.E.; Zois, N.E.; Falk, T.; Reimann, M.J.; Cirera, S.; Aupperle, H.; Oyama, M.A.; Olsen, L.H.
Highlights: First investigation of serotonin markers in an age-matched dog population grouped according to clinical MMVD status. A global investigation including the mitral valve, myocardium and serum serotonin. Analysis of markers in relation to gene expression and protein expression. Evidence of an association between 5-HT2BR gene expression in the mitral valve and myocardium and clinical MMVD. Abstract: Canine Myxomatous mitral valve disease (MMVD) is an age-related disease. Serotonin (5-HT) is implicated in the pathogenesis as locally-produced or platelet-derived. Involvement of the 5-HT2A receptor (R) and 5-HT2B R in the induction of myxomatous-mediating valvular myofibroblasts (MF) has been suggested. In an age-matched population of dogs with non-clinical and clinical MMVD, the objectives were to investigate (1) gene expression of 5-HT2A R and 5-HT2B R, (2) protein expression and spatial relationship of 5-HT2A R, 5-HT2B R and MF in the mitral valve (MV) and the cardiac anterior papillary muscle (AP) and (3) serum 5-HT concentrations. Gene expression of 5-HT2B R was significantly higher in MV and AP among dogs with clinical MMVD. This was not found for 5-HT2B R protein expression, though association of 5-HT2B R with myxomatous pathology and co-localization of 5-HT2B R and MF in MV and AP support a functional relationship, perhaps perpetuation of clinical MMVD. 5-HT2A R-expression and serum 5-HT showed no differences between groups.